PKM PENGENALAN SISTEM AKUNTANSI BIAYA PRODUKSI PADA USAHA JASA FAISAL TAILOR - Audrey M. Siahaan; Danri T. Siboro; Halomoan Sihombing; Vebry M Lumban Gaol; Victor H. Sianipar (Jurnal Abdimas Bina Bangsa, 2023)
SMEs at the time of determining the cost of production, do not understand how to calculate it. For MSMEs, they calculate their production costs based on their experience without knowing the type of business they are selling or creating. Faisal Services Business is a business that provides men's clothing sewing services. Abdimas proceeds by giving examples of how to calculate the cost of production for some of the sewing services provided. Service businesses perform production cost calculations according to the cost accounting concept. Faisal Service Business calculates the cost of raw materials and labor costs based on actual costs incurred, while factory overhead costs are calculated by determining the rate per item of service work